Activities of daily living assessment in spinal cord injury using the virtual reality system Toyra®: functional and kinematic correlations. Issue 1 (March 2016) - Dimbwadyo-Terrer, I.; Trincado-Alonso, F.; De los Reyes-Guzmán, A.; López-Monteagudo, P.; Polonio-López, B.; Gil-Agudo, A.
Abstract The main objective of this study was to analyze the correlations between functional scales and kinematic data collected during the execution of upper limb (UL) basic activities of daily living in an immersive virtual reality (VR) environment. Fifteen people with tetraplegia participated in the study. Moreover, we also want to confirm if changes in UL functional performance detected by functional scales are also detected by the VR system Toyra® . Patients were assessed before and after 4 weeks of daily conventional rehabilitation treatment complemented with a training with the VR system. Significant positive correlations between kinematic and functional parameters were found in the post assessment, verifying that changes in UL functional performance detected by functional scales are also measured by the VR system Toyra®, concretely the related to shoulder movements. Additionally, a predefined Agility metric has been applied, showing inversely proportional results to the level of injury, as we expected. The self-care category of the Spinal Cord Independence Measure (SCIM III) and the ranges of motion (ROM) captured with the VR system were analyzed, showing statistical significance changes between pre-post evaluations, supporting the hypothesis that kinematic analysis complements clinical and functional assessments of patients with tetraplegia.